PENGARUH KEPEMILIKAN KAS TERHADAP MANAJEMEN LABA RIIL DENGAN KONEKSI POLITIK SEBAGAI VARIABEL MODERASI - Ikhsan Ikhsan; Faisal Faisal; Cut Sri Firman Hastuti (Universitas Teuku Umar, 2021)
This study aims to provide evidence of the extent of cash holding ability in influencing real earnings management while also calculate the role of political connections as a moderating variable in companies listed on the Indonesia Stock Exchange in 2017 and 2018. This analysis is also supported by several control variables including profitability, company size, sales growth, and leverage. The sample selection method used in this study is purposive sampling in order to get a sample of 710 companies on the Indonesia Stock Exchange in 2017 and 2018. The analysis technique used is a technical analysis with a moderating regression analysis. Cash ownership is measured using the logarithm of the proportion of cash and cash equivalents with net assets, while net assets are measured by total assets minus cash and cash equivalents. Real earnings management (REM) is measured by calculating the number of Abnormal Cash Flow from Operations (Ab_CFO) plus Abnormal Discretionary Expenses (Ab_DEXP) and Abnormal Production Cost (Ab_PROD). While the disclosure of political connections is measured using a categorical scale (dummy). Based on the results of the regression test that has been done, cash holding has a positive and significant effect on real earnings management. Meanwhile, political connections do not affect real earnings management and political connections moderate the effect of cash holding on real earnings management. This study also provides information that disclosure of political connections can moderate the effect of cash holding on real earnings management appropriately in the entire sample studied. Keywords : Cash Holding, Real Profit Management, Political Connections, Profitability, Company Size, Sales Growth, and Leverage.